Integrated financing model in Islamic microfinance institutions for agriculture and fisheries sector - Aan Zainul Anwar (Investment Management & Financial Innovations, 2019)
The uniqueness of micro, small and medium enterprises (MSMEs) in the agriculture and fisheries sector has led to thoughts of innovation in the microfinance institutions (MFIs) that serve it. Service innovations in the agriculture and fisheries sector have been carried out in various countries to facilitate the development of this sector. This study aims to analyze the financing model of Islamic microfinance institutions (Islamic MFIs) based on the characteristics of the agriculture and fisheries sectors and the reconstruction of Salam contracts of Islamic financial institutions for farmers and fishermen. The research method used is qualitative descriptive analysis. The data were obtained through in-depth interviews with the agriculture and fisheries businesses in Central Java, Indonesia. The result showed that Salam contract constructed according to the characteristics of the fishing community to alleviate it from the shackles of moneylenders and wholesalers, including Islamic MFIs, farmers, and fishers as members of Islamic MFIs, buyers, Islamic banks and Islamic insurance. The output of this research is that farmers and fishermen can form a community to help one another with financial needs and are managed by Islamic MFIs that work in synergy with fisheries and agriculture companies, as well as an integrated Salam contract application system for Islamic MFIs.